Association between vitamin D status and asthma control levels among children and adolescents: a retrospective cross sectional study in Saudi Arabia - Abdullah Alolayan; Osama Al-Wutayd (BMC Pediatrics)
Abstract Background Asthma in children is one of the most common chronic disorders, with a significant impact on patients and their families. Few studies have been conducted in Saudi Arabia. This study aimed to determine the association between vitamin D status and asthma control. Additionally, it investigates the level of 25-hydroxy vitamin D (25(OH)D) and its associated factors among asthmatic children and adolescents in Qassim region. Methods This retrospective cross sectional study identified patients aged 1–15 years from January 2018 to January 2024, who attended pediatric clinics at Sulaiman Alhabib Hospital in Buraydah city, Qassim region, Saudi Arabia. Data on age, gender, body mass index (BMI), 25(OH)D levels, and seasonal variations were obtained from hospital records. Results A total of 431 asthmatic patients were identified, with a median [IQR] age of 9 [7–12] years. Among them, 268 (62.2%) had vitamin D deficiency (25(OH)D < 50 nmol/L; <20 ng/mL), with an overall median [IQR] 25(OH)D level of 42.6 nmol/L [31.6–58.8]; 17.0 ng/mL [12.6–23.5]. The median serum 25(OH)D level was highest in autumn and lowest in spring. Multiple linear regression analysis showed that participants aged 1–7 years (β = 19.3, 95% CI: 14.4 to 24.1, p < 0.001) and male participants (β = 4.9, 95% CI: 0.4 to 9.4, p = 0.033) had significantly higher 25(OH)D levels, whereas obese patients (β = -8.6, 95% CI: -14.7 to -2.6, p = 0.005), and those with 25(OH)D levels measured during the spring season (β = -6.5, 95% CI: -12.4 to -0.7, p = 0.029) had significantly lower 25(OH)D levels. The median [IQR] serum 25(OH)D levels for controlled, partially controlled, and uncontrolled asthma were 41.8 nmol/L [31–58]; 16.7 ng/mL [12.4–23.2], 43.6 nmol/L [30–61]; 17.4 ng/mL [12-24.4], and 45.2 nmol/L [30–57]; 18.1 ng/mL [12-22.8], respectively. Age, BMI, 25(OH)D levels, and seasonal variations were not found to be associated with asthma control levels. Conclusion Vitamin D deficiency was common among asthmatic children and adolescents. Lack of statistical association was observed between independent variables (age, gender, 25(OH)D levels, seasonal variations, and BMI) and asthma control in this setting. Routine assessment of vitamin D levels may not predict asthma control status.